SIMILE USED IN LENKA’S SONG EVERYTHING AT ONCE - Syarifah Syarifah; M. Manugeren; Purwarno Purwarno (Universitas Islam Sumatera Utara (UISU), 2020)
The research was related to figurative language but the researchers focused on simile, aimed at identifying the dominant type of simile used based on the theory put forward by Kennedy and Giola. Simile is a comparison of one thing to another which is always listed because the words